A compreensão da coordenação pedagógica sobre o ensino de valores na educação profissional - Araujo, Pandora Pimenta Hardt (2022)
The present research wanted to analyze whether and how the pedagogical coordinator understands the relationship between his work and the teaching of values in the teacher's training at school. First, we started with a bibliographic review of the literature (theses, dissertations, and articles), having as primary references the research of Gómez and Royo (2015); Borelli (2016); Nacasato, Bomfim, and De-Carli (2016); Silva (2016); Tognetta et al. (2017); Dias et al. (2018); Frick et al. (2019) and Siqueira (2019). Secondly, we studied documents from Brazilian educational legislation in the last five years, searching to understand the teaching of values, considering the training of teachers mainly in the context of professional education. Aristotelian understanding of ethics and values was our theoretical reference for the analysis. Considering the relevance of the pedagogical coordinators for the teacher's training in professional education, we choose them as our study's participants. The data production used survey research and discussion groups with pedagogical coordinators from a professional education school group in São Paulo. The analysis and interpretation of the data produced followed a qualitative approach in two stages: characterization of the participants (Pedagogical Coordinators) and mapping of their conceptions regarding teaching values and, later, categorization and analysis of the data produced by the discussion groups. We used the Prose Analysis method, formulated by André (1983). The results showed that although present in the regulation of different educational levels and viewed as relevant by the participants, teaching values still face challenges in their application to promote citizenship and acquire an emancipatory education. Finally, we proposed a possible training scheme to promote the teaching of values in the continuing training of the teachers, involving active methodologies and the exchange of experiences among peers, which would involve: • The design of the schools' Political Pedagogical Project (PPP); • Reflexive activities to align personal values to those defined in the PPP; • Recognition of constitutionally guaranteed human rights